ROPE and STRAW: Automatic Music Playlist Generators - Almeida, Marcos A. de; Vieira, Carolina C.; Melo, Pedro O. S. Vaz de; Assunção, Renato M. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
With the growth of multimedia content available on internet to users, music playlist generators is gaining importance nowadays. People search for ways to generate enjoyable playlists satisfying their tastes, and that suit the situation in which they are. Although many authors have proposed methods to generate music playlists satisfying certain restrictions, defining the qualities a good playlist should have is a difficult task. This paper revise and presents the implementation of a general method presented on literature that generates heterogeneous music playlists based on a simple input given by the user. The method was constructed to satisfy five quality constraints: heterogeneity, smooth transitions, novelty, usability and scalability. The tool is available on a website, where is posible to choose between two algorithms named ROPE and STRAW, and listen on YouTube to the playlist generated.